Increasing resilience in adolescents: the importance of social connectedness in adventure education programmes. (April 2017) - Scarf, Damian; Hayhurst, Jillian G; Riordan, Benjamin C; Boyes, Mike; Ruffman, Ted; Hunter, John A
Objective: Mental health problems are a leading cause of health-related disability during adolescence. The objectives of the current study were to investigate whether participating in an adventure education programme (AEP) increased adolescents' resilience and elucidate how social connectedness contributes to any increase. Method: Adolescents who participated in the AEP had their resilience measured on the first (Time 1) and last day (Time 2) of a 10-day voyage. Perceived social support and sense of belonging were also measured at Time 2. A control group of adolescents, who did not take part in the voyage, also had their resilience assessed at two time points, 10 days apart. Result: Adolescents who participated in the AEP, but not those in the control group, displayed an increase in resilience from Time 1 to Time 2. Further, the increase in resilience was related to the adolescents' sense of belonging, and this effect held when controlling for perceived social support. Conclusion: These findings demonstrate the positive impact AEPs have on adolescents' resilience and a mechanism through which this occurs.